Properties of Molybdenum Disulfide and Preparation Method - Liu, Zhiyuan (International Journal of Mechanical and Electrical Engineering, 2024)
Behind the development of integrated circuits to the current brilliant era is the contribution of Moore's Law, which has guided the development prospects of the industry for a long time. But as transistors continue to shrink in size and thickness, silicon itself approaches its own physical limits and Moore's Law no longer applies. Therefore, scientists are eager to solve this puzzle by introducing new materials, including two-dimensional materials. Molybdenum disulfide has attracted much attention because of its special properties, and the preparation method needs to be studied deeply for large-scale use of molybdenum disulfide. There are many factors that affect the synthesis of single layer molybdenum disulfide, such as the amount of reaction source, air pressure, substrate, reaction temperature of two sources, source heating rate, holding time, relative position between molybdenum source and sulfur source substrate, gas flow, etc. In short, these reaction conditions are summarized, which mainly affect the concentration and reaction speed of sulfur source and molybdenum source in the reaction substrate position. In this paper, the effects of CVD on the quality of single layer disulfide were summarized and its development trend was prospected.